Insights into the co-assemblies formed by different aromatic short-peptide amphiphiles. Issue 47 (23rd November 2021) - Gila-Vilchez, Cristina; Mañas-Torres, Mari C.; González-Vera, Juan A.; Franco-Montalban, Francisco; Tamayo, Juan A.; Conejero-Lara, Francisco; Cuerva, Juan Manuel; Lopez-Lopez, Modesto T.; Orte, Angel; Álvarez de Cienfuegos, Luis
Abstract : The mechanism of co-assembly of different aromatic dipeptides has been studied using a combination of microscopy and spectroscopy techniques. At an equimolar ratio, the kinetics of the process is favored giving rise to alternate copolymers. Abstract : We have investigated the co-self-assembly, in water and at room temperature, of different aromatic short peptides containing Fmoc- (fluorenylmethyloxycarbonyl-) and Nap- (2-(naphthalen-2-yloxy)acetyl) groups having also different chirality. Using a combination of spectroscopy and microscopy techniques we have shown that mixtures of peptides have a stronger preference to form co-assemblies giving rise to different types of fibrils of well-defined morphology. Kinetic analysis of fluorescence resonance energy transfer (FRET) between Fmoc- and Nap- side groups reported more information about the process of self-assembly between different dipeptides. We have shown that when peptides are mixed in an equimolar ratio, the kinetics of co-aggregation is faster than that occurring when the proportion is unbalanced. Moreover, following the emission band of Nap-excimers we have shown that these peptides form co-assemblies in an alternate fashion at an equimolar ratio. The mechanism of self-assembly has been studied by molecular dynamics and monitored by differential scanning calorimetry. The mechanical properties of the resulting composite hydrogels have been evaluated by rheology. These results show that the formation of co-assemblies is promoted by π–π interactions between the different aromatic groups resulting in accelerating polymerization due to destabilization of the intermediates.